The impact of new technologies and robotics on employment in the united states - N. E. Petrovskaya (Управление)
An analysis of the impact of new technologies on employment in the United States has been carried out. Various points of view on the prospects of job losses under the influence of automation and robotics have been shown. The paper uses methods of analysis, comparison, and expert evaluations. The study is based on data from the U.S. Bureau of Labor Statistics, the results of sample surveys of the American population. The article gives characteristics of the US labor force, considers its features. Examples of the use of new technologies by the largest American employers have been shown. New technologies are transforming all spheres from healthcare to transportation and manufacturing. New types of jobs are being created and the employment structure is changing. Untypical forms of employment are expanding.The paper provides public opinion survey on the attitude of Americans to artificial intelligence and its impact on their lives and work. The occurence of distance relations between the employee and the employer leads to the formation of a flexible and virtual labour market. The world of work is becoming increasingly digital. This process is causing fundamental changes in the world of work, which entails new challenges for various aspects of social policy. People of all ages will have to adapt to the new situation in the labour market, which is associated with technological changes and structural shifts in the demand for labour force. The importance and possibility of retraining, professional development, and career guidance throughout life have been updated. The study shows the importance of monitoring the impact of new technologies on employment in order to identify areas of risk.